Development and validation of the physical fitness test anxiety scale for college students - Yin, Shanshan; Tang, Fang; Gao, Pincao (Frontiers in Psychology, 2025)
ObjectiveThis study aims to develop and validate a Physical Fitness Test Anxiety Scale (FTAS) for Chinese college students and assess its scientificity and applicability through reliability and validity testing.MethodsThe initial scale was constructed through literature analysis and semi-structured interviews, followed by item analysis and factor analysis to optimize the scale structure. Multiple statistical methods were used to test the scale’s reliability and validity.ResultsThe final scale consists of 12 items, covering two dimensions: cognitive anxiety and somatic anxiety. The model fit was good (χ2/df = 2.29, RMSEA = 0.051, IFI, CFI, TLI, GFI, AGFI >0.90). The internal consistency coefficients for the total scale and the two dimensions ranged from 0.903 to 0.928, with split-half reliability between 0.804 and 0.899. The average variance extracted (AVE) ranged from 0.575 to 0.667, and the composite reliability (CR) ranged from 0.904 to 0.950.ConclusionThe Physical Fitness Test Anxiety Scale for college students has good reliability and validity and is suitable for assessing the physical fitness test anxiety levels of college students.